Proses Produksi Pembuatan dan Perakitan Mesin Pencacah Plastik - Vinky Try Octavia; Muhamad Ari; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Production process to build a machine must make some planning for the productionprocess to run effectively and efficiently. Production process is the activity of creating or addingusefulness product. Where the production process must be completed on time. Activity On Node(AON) method is a method used to create network planning in production process of a tool ormachine. Before creating a networked the first step is make group of activities undertaken during theproduction process. After that can determine the critical path in the production process. From thisstudy examines we learn how to create a network of plastic crusher machine by Activity On Node(AON) method. The results showed the production process and assembly of crusher plastic machineusing several machining processes such as turning, shaping, drilling and grinding. The assemblyprocess is done manually with the welding process. AON method (Activity On Node) got total workinghours equal to 114 hours that is 14.25 day and there are 9 critical path. The total cost requiredduring the production process of crusher plastic machine as a solution to reduce plastic waste is Rp.10.344.500,-.